Learning Islamic Religious Education in the Merdeka Curriculum: A Critical Review - Empaldi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the learning of Islamic Religious Education within the framework of the Merdeka curriculum. The method used in this study is a literature review that examines or reviews critically the knowledge, ideas, or findings contained in the body of academic-oriented literature, and formulates theoretical and methodological contributions for certain topics. The results of the study show that the Merdeka curriculum has a considerable influence on learning Islamic Religious Education, which is related to collaboration between subjects, using this kind of interdisciplinary approach certainly makes students' perspectives more open and broad which is useful for provisions in dealing with global world developments and the existence of challenges for educators and students.